O Pastor Peregrino: peregrinação como alegoria da penitência - Sanches, Angelo Moreno Bidigaray (2021)
The present study deals with the work O Pastor Peregrino (1608) by Francisco Rodrigues Lobo. Published in the early seventeenth century, O Pastor Peregrino is the second work of the pastoral trilogy of Rodrigues Lobo. The trilogy receives the title of the first book, A Primavera, of 1601 and is finalized with O Desenganado in 1614. Following the narrative trail left in A Primavera, the second volume of the plot tells the journey of Lereno’s pilgrimage, protagonist of the first two Works. Once a shepherd who lived in the margins of Lis and Lena, Lereno is thrown into exile unjustly by Amor and Ventura. During the narrative, the hero's pilgrimage acquires a distinct penitent character. An instrument of spiritual improvement, the journey is full of episodes in which the hero's patience and fidelity are put to the test. The end of the pilgrimage occurs when Lereno returns to the native land, where he is crowned, in the end, in return for his deeds From this conception, it was sought to investigate O Pastor Peregrino. During the work, through Avallec-Arce (1974) and other critics, the constitution of the pastoral novel is approached. From Hansen (2006), the question of allegory is addressed. In the end, through França, Nascimento and Lima (2017), the work of Kempis (2019) and other authors, the theological content of O Pastor Peregrino is demonstrated.